Effect of sea weed (Caulerpa racemosa) extract on biochemical variations, growth and yield of Vigna mungo - Abhilash, ES; Jisby, Jacob; Parayil, Sheeja P (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
The present investigations revealed that seaweed species were observed to be the potential sources of fertilizer. In the case of vigor index, at first 3 concentrations 100% was noticed and it reduced at last 2 concentrations. The phytotoxicity was increased with increased SLF concentration and it was at maximum at 3% concentration. Present findings encourage the application of such seaweeds as natural fertilizer in agriculture sector. It was also understood that the too much or too less concentrations of SLF has reduced effect on the selected plant. 1% concentration of Caulerpa racemosa SLF has proved increase in yield, growth and biochemical content in Vigna mungo. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9501 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 3-5